Estudo da clarificação da lecitina de soja - Castejon, Letícia Vieira (2010)
The soy lecithin, usually known as being a phosphorous group or phospholipids of the rude oil of soy. He/she possesses in his/her composition not only molecules lipids containing match molecules, but they count considerable amounts of chlorophylls, carotenes and brown substances. All these possess specific spectra of absorptions that for spectrophotometric can be quantified, therefore they supply characteristic coloration to the lecithin. The coloration is a brown darkness, a lot of times denominated of amber, it can be decisive factor in the choice and use of that natural emulsificant. Therefore, the coloration of the soy lecithin can be reduced through the addition of compositions chemical peroxides, which possess to structures (OO-²) of radical peroxides in their molecules, such as the peroxides of hydrogen (inorganic chemical bleach) and the benzoíla peroxides (organic chemical bleach). The application of the peroxides of hydrogen and of the benzyl peroxides as clarificant of the soy lecithin was studied and certain the minimum concentration was 0,5%, to the maximum of 2,0%. The analyses accomplished in the soy lecithin and in the samples treated with the bleaching agents were regarding the humidity tenors, saponification index, stability oxidative, composed chlorophylls, carotenes and brown substances. A preliminary test was accomplished soon in the beginning of the study, to determine which among ten solvents organic solubilized the lecithin to the maximum. The hexane was chosen as the appropriate for solubilization the soy lecithin in the physiochemical analyses of carotenes, brown substances and stability oxidative, because it possesses better custom/benefice, it is used thoroughly in the extraction of rude oil and it possesses characteristic of 100% of apolarity. The results obtained in the physiochemical analyses of the lecithin of added soy of peroxide of hydrogen to 35% in the proportions of 0,5%, 1,0%, 1,5% and 2,0% were: index bass of saponification, gradual increase in the stability oxidative for the decrease in the tenors of primary and secondary structures of the peroxidation reaction, degradation of compositions chlorophylls, decrease of the carotenes and of brown substances. To the peroxide of hydrogen to be decomposed it generates gas oxygen and free water, however the analysis on the humidity tenor was not satisfactory. And, regarding the results regarding the addition of peroxide of benzyl anidre 65% is had that the increase in the concentration of that it caused elevation of the saponification index, increase of the stability oxidative of the lecithin, suave degradation of composed chlorophylls and carotenes, besides reducing the amount of brown substances. Finally, at the end of the study the clarification terminology was determined as appropriate to describe the despigmentation of the soy lecithin with peroxide of hydrogen and benzyl peroxide visually e quantitivity with physic-chemistry analyses realized.